Contributions to the morphology and histology of the genital system of the pulmonate Agriolimax caruanae Pollonera - Sukkels, W. F.(Wilhelm Frederick) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1967.